One step synthesis of chromium-containing periodic mesoporous organosilicas and their catalytic activity in the oxidation of cyclohexane - Shylesh, S.; Srilakshmi, Ch.; Singh, A. P.; Anderson, B. G. (Microporous and Mesoporous Materials, 2007)
Chromium-containing ethane-bridged hybrid mesoporous materials (Cr-PMO) with uniform hexagonal arrangement were synthesized by two different synthesis routes using 1,2-bis(triethoxysilyl)ethane (BTEE) and tetraethyl orthosilicate (TEOS) as silica sources and alkyltrimethyl ammonium salts (ATMA) as surfactants. Powder X-ray diffraction, TEM, N-2 adsorption-desorption, FT-IR, in situ FT-Raman, UV-ViS, XPS, Si-29 MAS NMR and C-13 CP MAS NMR were used to probe the mesoporous structure and the nature of chromium sites in the hybrid catalyst matrix. PXRD, TEM and N-2 adsorption-desorption analysis showed that the original hexagonal structure of the materials is maintained after chromium substitution, while FT-Raman, UV-Vis and XPS analysis showed that chromium atoms exist in a highly dispersed state. The catalytic performance of the chromium-containing hybrid samples was tested in the liquid-phase oxidation of cyclohexane with aqueous hydrogen peroxide (H2O2) and non-aqueous tert-butylhydroperoxide (TBHP) as oxidants. The hybrid materials exhibited better catalytic activities and were more stable than the conventional Cr-MCM-41 catalyst. The higher catalytic activity of the new chromium-containing molecular sieves is attributed to the improved hydrophobicity of the materials and to the complementary structural features that facilitates the accessibility of cyclohexane to the active framework chromium sites. (c) 2006 Elsevier Inc. All rights reserved.
Keywords: Cr-MCM-41; Cr-PMO; Cyclohexane; hybrid mesoporous materials; Oxidation

Bridging the gap between micropores and mesopores by the controlled transformation of bifunctional periodic mesoporous silicas - Shylesh, S.; Srilakshini, Ch.; Singh, A. P.; Anderson, B. G. (Microporous and Mesoporous Materials, 2008)
Novel bifunctional periodic mesoporous silicas having high content of organic groups in the pore channels and chromium in the frame wall has been synthesized by direct co-condensation method, using organo trialkoxysilanes (chloro propyl, vinyl, methyl), chromium nitrate and tetraethyl orthosilicate, in presence of cetyltrimethyl ammonium surfactants. The obtained materials show one main peak in the XRD patterns up to a molar ratio of 1: 1 between TEOS and organosilane in the synthesis gel and N-2 adsorption-desorption analysis shows that the mesopore structure remains intact after the surfactant removal process. Among the organosilanes, chloro propyl and vinyl pendant chromium samples shows a shift in the main peak to higher 2-theta values with a corresponding decrease in pore volume and pore diameter, with the percentage of organosilane functionalization. Small-pore silicas and chromium silicas can be prepared from the large pore mesoporous MCM-41, by effectively removing the organic groups by calcination. By this method, the pore size of the material can be tailored into the super-microporous region, without changing the chain length of the surfactant used in the assembly process. The shrinkage in pore size is dependent on the nature and percentage of the organic pendant groups that the chloro propyl and vinyl pendant mesoporous materials show the maximum pore size shrinkage than the small chain length methyl units. Because of the tailorable pore size and with better textural characteristics, chromium-silica materials find applications in the field of shape selective heterogeneous catalysis, as demonstrated in the oxidation reaction of cyclohexane, than the conventional metal-containing mesoporous materials. (c) 2007 Elsevier Inc. All rights reserved.
Keywords: bifunctional silicas; chromium; Cyclohexane; MCM-41; Oxidation